1994
DOI: 10.1016/0375-9474(94)90370-0
|View full text |Cite
|
Sign up to set email alerts
|

Dilepton production in nucleon-nucleon interactions

Abstract: Starting from a realistic one-boson-exchange-model fitted to the amplitudes of elastic nucleon-nucleon scattering and the process N N → N ∆ we perform a fully relativistic and gauge invariant calculation for the dilepton production in nucleon-nucleon collisions, including the important effect of propagating the ∆-resonance. We compare the results of our calculations with the latest experimental data on dilepton production. We also show how to implement various electromagnetic formfactors for the hadrons in our… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(121 citation statements)
references
References 22 publications
3
117
1
Order By: Relevance
“…At this energy also the interference between nucleon and ∆-pole terms is negligible. At high energies, where this interference becomes important [47], however, the overall contribution from these channels is negligible (see below). We, furthermore, discard e + e − production from the scalar mesons f 0 , a 0 as advocated in Ref.…”
Section: Dilepton Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this energy also the interference between nucleon and ∆-pole terms is negligible. At high energies, where this interference becomes important [47], however, the overall contribution from these channels is negligible (see below). We, furthermore, discard e + e − production from the scalar mesons f 0 , a 0 as advocated in Ref.…”
Section: Dilepton Productionmentioning
confidence: 99%
“…In this case the strong interaction part and the electromagnetic part separate; however, the cross section for dileptons has to be corrected [45,46] by reducing the phase-space for the colliding particles in their finalstate. We discard pp bremsstrahlung from the nucleon pole since the microscopic OBE calculations [47,48,49] have shown that at 1.0 GeV the pp bremsstrahlung is smaller than the ∆ Dalitz decay contribution by a factor of 2-3. At this energy also the interference between nucleon and ∆-pole terms is negligible.…”
Section: Dilepton Productionmentioning
confidence: 99%
“…Since we use these Lagrangians to directly model the T-matrix, we have also included a nucleon-nucleon-axial-vector-isovector vertex, with the effective Lagrangian given by 6) where A represents the axial-vector meson field. This term is introduced because in the limit of large axial meson mass (m A ) it cures the unphysical behavior in the angular distribution of N N scattering caused by the contact term in the one-pion exchange amplitude [33], if g N N A is chosen to be…”
Section: Formalismmentioning
confidence: 99%
“…Initial interaction between two incoming nucleons is modeled by an effective Lagrangian which is based on the exchange of the π, ρ, ω and σ mesons. The coupling constants at the nucleon-nucleon-meson vertices are determined by directly fitting the T-matrices of the nucleon-nucleon (N N ) scattering in the relevant energy region [33]. The effective-Lagrangian uses the pseudovector (PV) coupling for the nucleon-nucleon-pion vertex (unlike the resonance model [22]), and thus incorporates the low energy theorems [34] of current algebra and the hypothesis of partially conserved axial-vector current (PCAC).…”
Section: Introductionmentioning
confidence: 99%
“…Superimposed on our data is a calculation 14 by Haglin who uses the results of reference [12]. Another calculation by Schafer et al, 15 using a fit to elastic nucleon-nucleon data, also reproduces the general behavior of the ratio data. The behavior of the ratio as a function of energy is shown in Figure 3.…”
Section: Proton-proton and Proton-deuteron Programmentioning
confidence: 97%